THE USE OF CONTEXT CLUES IN IMPROVING STUDENTS’ READING ABILITY - Fariska Wulandari (IKIP PGRI Pontianak, 2017)
This research was aimed to find out whether context clues can improve the students’ reading ability and how significant’s context clues in improving students’ reading ability at third semester students of Agriculture Technology Polytechnic of Tonggak Equator Pontianak. This research was classroom action research which was set out in two cycles. The subjects involved included the third semester students of Agriculture Technology Department, Polytechnic of Tonggak Equator. In collecting the data, the researcher used field note and test. The data of the students’ pre-test and progress test score were analyzed by using mean score and the data of observation was analyzed descriptively. The finding of this research was the students’ reading ability was improved from pre-test and progress test from cycle to cycle. The mean score of the students’ pre-test was 51.8. Then, the mean score of the students’ progress test in the first cycle was 77.6. Finally, the mean score of the students’ progress test in the second cycle was 88.8. Then, the rocords from the field note supported the finding from pre-test and post-test was the students’ reading ability improved from the first cycle to the second cycle after implementation of the treatment by researcher.Keywords: improving, reading ability, context clues.